2002
DOI: 10.1186/1475-2875-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of drug-resistant Plasmodium falciparum from Thailand

Abstract: BackgroundThe increasing levels of Plasmodium falciparum resistance to chloroquine (CQ) in Thailand have led to the use of alternative antimalarials, which are at present also becoming ineffective. In this context, any strategies that help improve the surveillance of drug resistance, become crucial in overcoming the problem.MethodsIn the present study, we have established the in vitro sensitivity to CQ, mefloquine (MF), quinine (QUIN) and amodiaquine (AMQ) of 52 P. falciparum isolates collected in Thailand, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Polymorphisms in the dhfr and dhps genes were genotyped by the PCR and restriction fragment length polymorphism method previously described by Lopes et al [ 21 ], Figueiredo et al [ 22 ] and Mendes et al [ 23 ]. For the dhfr gene, DNA fragments of 206, 320 and 504 bp were amplified by PCR for codons 51, 59 and 108, respectively, using codon-specific primers (table 1 ), while for the dhps gene, a common DNA fragment of 438 bp was amplified for codons 437 and 540, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Polymorphisms in the dhfr and dhps genes were genotyped by the PCR and restriction fragment length polymorphism method previously described by Lopes et al [ 21 ], Figueiredo et al [ 22 ] and Mendes et al [ 23 ]. For the dhfr gene, DNA fragments of 206, 320 and 504 bp were amplified by PCR for codons 51, 59 and 108, respectively, using codon-specific primers (table 1 ), while for the dhps gene, a common DNA fragment of 438 bp was amplified for codons 437 and 540, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…DNA samples were also genotyped at pfmdr1 codons 86, 184, 1034, and 1042 for single nucleotide polymorphism (SNP) analysis by real-time PCR on an ABI sequence detector 7000 (Applied Biosystems, Warrington, United Kingdom), as previously described (28). Samples were also probed for an additional pfmdr1 SNP (Y1246D) using a PCR-restriction fragment length polymorphism method (29). The clinical isolates were also screened for the K76T point mutation in the P. falciparum chloroquine resistance transporter gene 1 (pfcrt1) using real-time PCR (30).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, apart from changed expression, there is also evidence to suggest that single nucleotide polymorphisms in the pfmdr1gene may modulate parasite susceptibility to quinine, mefloquine and halofantrine. A mutation at codon 86 (N84Y) was associated with increased mefloquine sensitivity in P. falciparum from Thailand [52,53] and the Gambia [54]. Genetic crossing experiments have shown that polymorphisms at codon 184 (F to Y) and 1042 (D to N) in the Pgh-1 protein are associated with increased sensitivity to both mefloquine and halofantrine [55].…”
Section: Resistancementioning
confidence: 98%